A Model for Assessment of Transient Stability of Electrical Power System - Ajenikoko Adedayo Ganiyu; Anthony A. Olaomi (Institute of Advanced Engineering and Science, 2014)
The stability of a system is its ability to return to normal or stable operation after having been subjected to some forms of disturbances. A disturbance in a power system is a sudden change or sequence of changes in one or more of the physical quantities. In this paper, the transient reactance of a synchronous machine, mechanical input power, kinetic energy of a rotating body, moment of inertia, angular acceleration, angular displacement and the rotor displacement angles were used as input parameters for the development of the Transient Stability model..The model is validated with a single machine system, a 2-machine system and a multi-machine system. The results of the work showed that the single machine system supplying an infinite bus-bar fluctuates while the 2-machine system remains unstable throughout the period. Generator 3 of the multi-machine system experienced the most violent swing, pulled out of synchronism during the first swing thus making the system to be unstable. The Transient Stability Model developed can be used for effective planning and operation of power systems.DOI:http://dx.doi.org/10.11591/ijece.v4i4.5850